SHAPE OPTIMIZATION OF NONLINEAR CURVED BEAM AND DESIGN OF CONSTANT PRESSURE SUPPORT DEVICE - XIE Miao; ZHANG WenZhuo; Ll WeiDong; LlU Jie; ZHOU QingHai; XING XuWen (Jixie qiangdu)
Based on the top beam support structure of advance support equipment, a design method of constant pressure support device is studied. The constant pressure support device is composed of positive stiffness linear spring, negative stiffness nonlinear plane curved beam and pressure bearing air bag. The characteristics of Nonlinear Plane Curved Beam with negative stiffness are briefly described by using B-spline curve. Based on genetic algorithm and nonlinear finite element method , the shape of the nonlinear plane curved beam with negative stiffness is designed and optimized. According to the working principle of constant pressure support, the stiffness and strength properties of the linear coil spring are analyzed and designed. The components of the constant pressure support device are designed to realize the constant output pressure and self-protection function of the support device. The constant pressure support design method proposed in this paper provides strong technical support for the development of advanced support in the fully mechanized mining road.